Analisis Nilai-Nilai Filsafat Rasionalisme dalam Buku Fahruddin Faiz - Bagus Astaman, Raden (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
Philosophy is a subject of study that is widely discussed. Many philosophical texts attract attention. One Muslim scholar who has written many books on philosophy, namely Dr. Fahruddin Faiz, one of the books that talks about rationalism is a book entitled "Disappearing, Finding Your True Self". In this research, the writer wants to examine more deeply about the values of the philosophy of rationalism contained in his work. The focus of this research is How the description of the book Disappears, Finds Your True Self by Dr. Fahruddin Faiz How to Analyze the Values of Rationalism Philosophy in Dr. Fahruddin Faiz. The purpose of this research is to find out the substance of the book: Disappearing, Finding Your True Self by Dr. Fahruddin Faiz. Analyzing Dr.'s thoughts. Fahruddin Faiz on the Philosophical Values of Rationalism in the Book Disappearing, Finding Your True Self. In this study, the authors used a type of library research (library research). The object of this research is the values of the philosophy of rationalism in Dr. Fahruddin Faiz's book entitled Disappearing to Find Your True Self. This research activity is in the form of reading text books, listening to online seminars on reviewing the book and the author recognizes, identifies ideas and main ideas so that they become a whole meaning and find philosophical values. The results of this study are to explain that in the book Disappearing to Find Your True Self there are several values originating from Rene Descartes, namely, Principles and Motto of Life, starting to philosophize, finding true truth through reason, thinking is innate ideas, Cartesian ethics which explains God , Mind and Matter, then about philosophical advice. Also explained that Fahruddin Faiz is an expert in Islamic philosophy who wrote this book with a passing approach, namely the method of seeing the truth of one thing with another perspective of truth. The climax lies in the similarity value in every spiritual teaching.